DOI: 10.26686/wgtn.17145788
|View full text |Cite
|
Sign up to set email alerts
|

Toward Inclusive and Equitable Education for All: Lessons from the experiences of New Zealand refugee background university students

Abstract: <p>The ability of education to transform individuals' lives, and by extension those of their communities and societies, is well documented. As such, education is at the heart of the United Nations’ (2015) Sustainable Development Goals (SDGs), represented by SDG 4, “Quality Education”, which seeks to ensure inclusive and equitable quality education to promote lifelong learning opportunities for all. Tertiary education institutions (TEIs) in particular have been highlighted as critical settings from which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(252 reference statements)
0
2
0
Order By: Relevance
“…These are however indicators for potential future mentorship program participation and have little relative brand visibility or student recruitment enhancement (Quadt et al, 2023). This analysis showed that there is a clear directional influence of the UAUT mentorship program activities on mentee groups as the brand visibility and student recruitment impacts were only evident at actions that lead mentees to UAUT and actions by UAUT stakeholders to provide guidance for post-secondary school education options at UAUT (Willette, 2020).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…These are however indicators for potential future mentorship program participation and have little relative brand visibility or student recruitment enhancement (Quadt et al, 2023). This analysis showed that there is a clear directional influence of the UAUT mentorship program activities on mentee groups as the brand visibility and student recruitment impacts were only evident at actions that lead mentees to UAUT and actions by UAUT stakeholders to provide guidance for post-secondary school education options at UAUT (Willette, 2020).…”
Section: Resultsmentioning
confidence: 88%
“…Several students also correctly identified UAUT as the sponsor for the I am the Future youth activities, a secondary school student career development program (Quadt et al, 2023). This heightened awareness on brand visibility for the specific activities was attributed to the good use of colors and branding on the publicity materials and the personal persuasion of the coordinators in approaching UAUT students to help with the activities (Willette, 2020). The mentorship coordinators were also reported to have encouraged the mentees and their parents to attend UAUT open days to learn about the courses offered at UAUT (Hsiao et al, 2024).…”
Section: Resultsmentioning
confidence: 99%